PENGEMBANGAN MEDIA PEMBELAJARAN FISIKA MENGGUNAKAN SWISH MAX4 MEMAHAMI KONSEP MOMENTUM IMPULS DAN TUMBUKAN DI SMA - Yanti, Febri; Astalini, Astalini; Kurniawan, Wawan (EduFisika: Jurnal Pendidikan Fisika, 2019)
The research aims to develop physics learning media using SWiSH Max4 a valid and viable class of collision impulse momentum material X MIPA SMA. This type of research was research and development. The steps in the development of Luther include: concept, design, material collecting, assembly, and testing. The subject of the research trials was the students XMIPA4 SMA 11 Jambi City. Data collection instruments using material validation sheets, media and student perception quisionare. Data were analyzed descriptively. The Media developed has flash, movie and EXE formats. The material was presented with text, images, video and animation. Media and material validation results are declared feasible by the validator. Score analysis of the students' perceptions for educational aspects, achieving a score of 135 (very good), the display aspect of the program 138.8 (very good), and the aspect of the technical quality of 132.3 (very good). Physics learning Media using SWiSH Max4 is valid and well worth use.